Treatment of post-traumatic stress disorder with eye movement desensitization and reprocessing: Outcome is stable in 35-month follow-up - Högberg, Göran; Pagani, Marco; Sundin, Örjan; Soares, Joaquim; Åberg-Wistedt, Anna; Tärnell, Berit; Hällström, Tore (Psychiatry research, 2008)
Post-traumatic stress disorder (PTSD) is an anxiety disorder that may follow major psychological trauma. The disorder is longstanding, even chronic, and there is a need for effective treatment. The most effective short-term treatments are cognitive behavioural therapy and eye movement desensitization and reprocessing (EMDR). Twenty subjects with chronic PTSD following occupational health hazards from “person under train” accidents or assault at work were treated with five sessions of EMDR. They were assessed with psychometric scales and diagnostic interviews before treatment, directly after treatment, at 8 months, and at 35 months after the end of Therapy. The primary outcome variable was full diagnosis of PTSD according to the DSM-IV diagnostic criteria. Results from interview-based and self-evaluation psychometric scales were used as secondary outcome variables. Immediately following treatment, the patients were divided up into two groups, initial remitters (12 of 20) and non-remitters (8 of 20). There were no drop-outs during therapy, but three patients withdrew during follow-up. The initial result was maintained at the 35-month follow-up. The secondary outcome variables also showed a significant immediate change towards normality that was stable during the long-term follow-up. After 3 years of follow-up, 83% of the initial remitters had full working capacity.